Drug induced anxiety and depression in patients treated for chronic hepatitis C - Farooq, Muhammad Ahsan; Mehmood, Asif; ., Israr Ul Haque; Hameed, Muhammad Asim; Ahmed, Umair (Journal of Fatima Jinnah Medical University, 2019)
Background: Depression is common in patients treated for Hepatitis C who receive interferon and ribavirin. This has been a major challenge in past for treatment compliance. Depression is believed to be less common with newer direct acting antivirals. This study aims to compare different regimens for drug induced anxiety and depression using Hospital Anxiety and Depression Scale (HADS) questionnaire. Subjects and Methods: This observational study was done at Lahore General Hospital, Lahore from 1st January 2016 till 15th February 2017. A total of 126 patients of chronic Hepatitis C requiring treatment with no baseline depression or anxiety as assessed by HADS questionnaire were enrolled. Patients were divided in 3 groups depending upon their treatment regimen. Two regimens were pegylated interferon based while one was interferon free using sofosbuvir. All patients completed their treatment. Frequency of anxiety and depression were evaluated using HADS questionnaire at the end of treatment. Results: A total of 126 patients, 44 males and 82 females, were enrolled; of these 62 (49.2%) received Pegylated interferon (PEG-IFN) + ribavirin, 27 (21.4%) received PEG-IFN + ribavirin+ sofosbuvir and 37 (29.4%) received sofosbuvir + ribavirin. Out of 126 patients, 40 (31.7 %) had definite anxiety at end of treatment while 46 (36.5%) had definite depression at end of treatment. Definite anxiety and depression were significantly low in sofosbuvir+ ribavirin group. Conclusion: Anxiety and depression are much less common with direct acting antivirals than interferon-based regimens for chronic hepatitis C treatment.